Four Classes of Two Weight Threefold Linear Codes - Banu, P. Shakila; Srirekha, K. (International Journal of Aquatic Research and Environmental Studies, 2026)
This work presents four classes of two weight threefold linear codes over the ring Fq + uFq. By applying the Gray map, four classes of two weight threefold linear codes over Fq are constructed. These resulting linear codes achieve optimality with respect to the Singleton and Griesmer bounds. Furthermore, a comparison between the Singleton and Griesmer bounds is established.